E-retailing of restaurant services: pricing strategies in a competing online environment. Issue 11 (1st November 2016) - Zheng, Xiabing; Guo, Xiaolong
Abstract: Establishing online channels and providing online discounts by building business partner relationships with third-party websites have emerged as important and effective marketing strategies in the restaurant industry. This study examines the optimal pricing strategy of restaurants in a competing environment when they participate in this relationship with a third-party website. Results suggest that neither participation nor online price discount should be encouraged for all restaurants. In particular, for a restaurant with a fixed service capacity, participation and online price discount are recommended when the number of offline loyal customers is relatively small. With the increase in the number of loyal offline customers, the optimal online discount rate decreases, whereas the unit commission fee for the third-party website remains constant. When the optimal discount rate reaches zero, the optimal decision for the restaurant is to decrease the unit commission fee. Based on these findings, this study analytically provides the optimal pricing strategies for restaurants and the corresponding boundaries for the strategy set.